2007
DOI: 10.1128/aem.01533-07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Biomass, Plant Diversity, and Water Content on Bacterial Communities in Soil Lysimeters: Implications for the Determinants of Bacterial Diversity

Abstract: Soils may comprise tens of thousands to millions of bacterial species. It is still unclear whether this high level of diversity is governed by functional redundancy or by a multitude of ecological niches. In order to address this question, we analyzed the reproducibility of bacterial community composition after different experimental manipulations. Soil lysimeters were planted with four different types of plant communities, and the water content was adjusted. Group-specific phylogenetic fingerprinting by PCR-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
36
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 61 publications
6
36
0
2
Order By: Relevance
“…The DGGE profiles demonstrated that our inoculation procedure reestablished a diverse bacterial community, containing all major groups of rhizosphere bacteria (Zul et al, 2007) in our Magenta system. Cloning and matching of the sequences to excised bands proved not only the presence of a diverse range of different phylogenetic groups but even of uncultured bacteria, suggesting a successful establishment of natural microbial communities in our experimental systems.…”
Section: Discussionmentioning
confidence: 99%
“…The DGGE profiles demonstrated that our inoculation procedure reestablished a diverse bacterial community, containing all major groups of rhizosphere bacteria (Zul et al, 2007) in our Magenta system. Cloning and matching of the sequences to excised bands proved not only the presence of a diverse range of different phylogenetic groups but even of uncultured bacteria, suggesting a successful establishment of natural microbial communities in our experimental systems.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains were isolated by streaking liquid cultures onto the medium described above, solidified with gellan gum (8 g l 21 ; Sigma-Aldrich Chemie). One of the cultured betaproteobacteria, strain byr23-80 T , was selected for further characterization since it occurred in association with higher plants (Zul et al, 2007). Subsequent physiological, biochemical and phylogenetic characterization revealed that the isolate represents a novel member of the genus Massilia within the family Oxalobacteraceae of the order Burkholderiales.…”
mentioning
confidence: 99%
“…Strain byr23-80 T was isolated during the investigation of bacterial communities in soil lysimeters (Zul et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The medium was spiked with the inducer molecules cyclic AMP (cAMP), N-(oxohexanoyl)-DL-homoserine lactone (OHHL) and N-(butyryl)-DL-homoserine lactone (BHL), each at a final concentration of 10 mM (Bruns et al, 2003a). Each culture was inoculated with 50 bacterial cells and incubated at 15 u C. Enrichments were screened for the presence of acidobacteria by group-specific PCR after lysis of the cells by six consecutive freeze-thaw cycles, employing primers 31F and 341r and the conditions described previously (Zul et al, 2007). One of the positive enrichments was chosen to isolate strain Jbg-1 T on agarsolidified HD medium (1 : 10-diluted; 0.05 % casein peptone, 0.01 % glucose, 0.025 % yeast extract, w/v).…”
mentioning
confidence: 99%